ANTESEDEN NIAT MELAKUKAN PEMBELIAN ULANG PRODUK SECARA ONLINE DI INDONESIA - , Ignatius Hari Santoso, SE., Prof. Dr. Jogiyanto H.M., M.B.A., Ak ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Online buying activity is increasing along with the increasing of internet based information technology. This gives benefit to online businessman and businesswoman. However the efforts which should be given are harder than before because of the increasing of online criminality which happened in Indonesia. The objective from this study generally is to reveal the antecedents of online repurchase intention in Indonesia This study is using 170 respondents which have experience in online purchasing at least one times before. Visual Partial Least Square is used to examine the relationship between construct. From 17 hypotheses which have been proposed, five among them are not supported. There are relationship between perceived system quality toward online repurchase intention, relationship between perceived service quality toward online shoppersâ trust, relationship between perceived information quality toward online shoppersâ satisfaction, relationship between perceived price toward online shoppersâ satisfaction and relationship between perceived price toward online repurchase intention. Generally this study conclude that the developed model which used in this study can be used to predict online repurchase intention even several relationship is found not significant. Another conclusion from this study is perceived information quality, perceived service quality, subjective norms, online shopperâs trust, and online shoppersâ satisfaction are the antecedents of online repurchase intention.